Montalvo, la reflexión ética y la producción intelectual - Andocilla L, Marcelo H. (2017)
Juan Montalvo continues awakening the interest of past and present generations; it’s one of the most inﬂ uential Ecuadorian authors in Latin America. The present essay tries to approach the montalvina work from an area close to the philosophy: the ethics; and from this, the formation of the ethical character that Montalvo demonstrated in his work and life, as well as the interrelations he established in his controversy over literary creation that could well extend to scientiﬁ c creation and publication of its results